2001
DOI: 10.1002/pits.1037
|View full text |Cite
|
Sign up to set email alerts
|

Body dissatisfaction, drive for thinness, and self‐esteem in African American college females

Abstract: Ninety‐five African American undergraduate females who were attending three predominately Caucasian universities were evaluated for body dissatisfaction and drive for thinness as well as on four dimensions of self‐concept (physical, social, academic, and personal competence). The participants were largely middle class, with 78% reporting parental education levels between high school to college graduation. Results indicated body dissatisfaction and drive for thinness at levels commensurate with Caucasian sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 19 publications
1
21
1
Order By: Relevance
“…The second most powerful predictor was the risk factor Drive for Thinness, with Physical Self-concept and Drive for Thinness accounting for 52% of the variance in Body Dissatisfaction. This finding is consistent with previous research implicating endorsement of the thin ideal as a risk factor for body dissatisfaction (James et al, 2001;Phelps, Johnston, et al, 1999b) and eating-disordered behavior (Killen et al, 1994). Furthermore, the predictive power of the pursuit of the thin ideal fits theoretical models implicating the media's influence on the vulnerable female.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The second most powerful predictor was the risk factor Drive for Thinness, with Physical Self-concept and Drive for Thinness accounting for 52% of the variance in Body Dissatisfaction. This finding is consistent with previous research implicating endorsement of the thin ideal as a risk factor for body dissatisfaction (James et al, 2001;Phelps, Johnston, et al, 1999b) and eating-disordered behavior (Killen et al, 1994). Furthermore, the predictive power of the pursuit of the thin ideal fits theoretical models implicating the media's influence on the vulnerable female.…”
Section: Discussionsupporting
confidence: 91%
“…Hierarchical regression analysis revealed that Physical Self-concept alone accounted for 45% of the variance in Body Dissatiskction. These and previous findings suggest that Physical Self-Concept may be a strong protective factor in deterring eating-disordered behavior (James et al, 2001;Klingenspor, 1994;Phelps, Johnston, et al, 1999).…”
Section: Discussionmentioning
confidence: 81%
“…The absence of results is unexpected given past research that highlighted the protective, body-affirming aspects of African-American and Latina culture (Abrams, Allen, & Gray, 1993;Lopez, Blix, & Blix, 1995;Parker et al, 1995). More recent studies have demonstrated that eating disorders are present in diverse cultural groups (James, Phelps, & Bross, 2001;Perez, Voelz, Pettit, & Joiner, 2002). The absence of a significant relationship between race and disordered eating illustrates the value of a more nuanced understanding of the role of ethnic identity in protecting against disordered eating (Shuttlesworth & Zotter, 2011).…”
Section: Discussioncontrasting
confidence: 48%
“…In addition, another study has suggested that AA acculturation to White culture can increase their vulnerability to White beauty norms (Abrams, Allen, & Gray, 1993). Another study found that AA women at predominately Caucasian universities reported an internalization of the dominant cultural ideal of thinness and beauty (James, Phelps, and Bross 2001;Lester and Petrie 1998).…”
mentioning
confidence: 96%